Implementation of continuous-wave Doppler ultrasound to detect the high-risk foetus in the low-risk mother: lessons from South Africa - Tsakane M.A.G. Hlongwane; Robert C. Pattinson; Anne-Marie Bergh (BMC Pregnancy and Childbirth, 2023)
Abstract Introduction Detecting the risk of stillbirth during pregnancy remains a challenge. Continuous-wave Doppler ultrasound (CWDU) can be used to screen for placental insufficiency, which is a major cause of stillbirths in low-risk pregnant women. This paper describes the adaptation and implementation of screening with CWDU and shares critical lessons for further rollout. Screening of 7088 low-risk pregnant women with Umbiflow™ (a CWDU device) was conducted in 19 antenatal care clinics at nine study sites in South Africa. Each site comprised a catchment area with a regional referral hospital and primary healthcare antenatal clinics. Women with suspected placental insufficiency as detected by CWDU were referred for follow-up at the hospital. A 35–43% reduction in stillbirths was recorded. Methods The authors followed an iterative reflection process using the field and meeting notes to arrive at an interpretation of the important lessons for future implementation of new devices in resource-constrained settings. Results Key features of the implementation of CWDU screening in pregnancy combined with high-risk follow-up are described according to a six-stage change framework: create awareness; commit to implement; prepare to implement; implement; integrate into routine practice; and sustain practice. Differences and similarities in implementation between the different study sites are explored. Important lessons include stakeholder involvement and communication and identifying what would be needed to integrate screening with CWDU into routine antenatal care. A flexible implementation model with four components is proposed for the further rollout of CWDU screening. Conclusions This study demonstrated that the integration of CWDU screening into routine antenatal care, combined with standard treatment protocols at a higher-level referral hospital, can be achieved with the necessary resources and available maternal and neonatal facilities. Lessons from this study could contribute to future scale-up efforts and help to inform decisions on improving antenatal care and pregnancy outcomes in low- and middle-income countries.